Evaluating the structural reform of outpatient psychotherapy in Germany (ES-RiP trial) - a qualitative study of provider perspectives - Poß-Doering, Regina; Hegelow, Martin; Borchers, Milena; Hartmann, Mechthild; Kruse, Johannes; Kampling, Hanna; Heuft, Gereon; Spitzer, Carsten; Wild, Beate; Szecsenyi, Joachim; Friederich, Hans-Christoph (BMC health services research, 2021)
Access to outpatient mental healthcare can be challenging for patients. In Germany, a national structural reform was implemented in 2017 to accelerate and enhance access to outpatient psychotherapy and reduce waiting times. During the first phase of the study ‘Evaluation of a structural reform of the outpatient psychotherapy guideline (ES-RiP)’ and embedded into a process evaluation, the implementation was to be evaluated through assessing general practitioners’ (GPs) and psychotherapists’ (PTs) perspectives regarding utilization of provided new measures, and perceived potential for optimization. Particular focus was on patients with a comorbidity of mental disorders and chronic physical conditions (cMPs).
Gesehen am 08.12.2021